2010
DOI: 10.1186/1750-1326-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β-Acetylcholinesterase complexes potentiate neurodegenerative changes induced by the Aβ peptide. Implications for the pathogenesis of Alzheimer's disease

Abstract: The presence of amyloid-β (Aβ) deposits in selected brain regions is a hallmark of Alzheimer's disease (AD). The amyloid deposits have "chaperone molecules" which play critical roles in amyloid formation and toxicity. We report here that treatment of rat hippocampal neurons with Aβ-acetylcholinesterase (Aβ-AChE) complexes induced neurite network dystrophia and apoptosis. Moreover, the Aβ-AChE complexes induced a sustained increase in intracellular Ca2+ as well as a loss of mitochondrial membrane potential. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 47 publications
0
84
0
1
Order By: Relevance
“…Moreover, the AChE gets infused stereotaxically into CA1 region of the rat hippocampus and induces the formation of plaque-like structures and directly promotes the deposition of Ab plaques. More recently, it has been demonstrated that Ab-AChE complexes are more toxic than Ab fibrils alone and neurons treated with Ab-AChE complex showed a neurite network more highly disrupted than one treated with Ab alone (Dinamarc et al, 2010). In addition to that, the activity of BuChE has been found to be increased during the later stages of plaque maturation, which subsequently results in neuronal degeneration (Guillozet et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the AChE gets infused stereotaxically into CA1 region of the rat hippocampus and induces the formation of plaque-like structures and directly promotes the deposition of Ab plaques. More recently, it has been demonstrated that Ab-AChE complexes are more toxic than Ab fibrils alone and neurons treated with Ab-AChE complex showed a neurite network more highly disrupted than one treated with Ab alone (Dinamarc et al, 2010). In addition to that, the activity of BuChE has been found to be increased during the later stages of plaque maturation, which subsequently results in neuronal degeneration (Guillozet et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidences illustrate that AChE accelerates aggregation of Ab peptide and formation of Ab-AChE complex at the synaptic region of hippocampus leading to DOI: 10.3109/13880209.2015.1017886 neuronal degeneration (Dinamarca et al, 2010;Reyes et al, 2004). Symptomatic treatment for AD involves potentiation of cholinergic activity through the inhibition of AChE (Rahman & Choudhary, 2001).…”
Section: Acetylcholinesterase and Butyrylcholinesterase Inhibitory Acmentioning
confidence: 99%
“…Moreover, Wu et al (2012) reported the blood-brain permeability of catechins, which illustrates that catechins can act as drug for the treatment of AD. Scientific evidences have illustrated AChE inhibitor as most viable therapeutic target for symptomatic improvement in AD because AChE not only enhances the cholinergic neurotransmission in the brain but also reduce the aggregation of b-amyloid, the key factor in AD (Dinamarca et al, 2010). Recent reports have showed that in addition to cholinergic deficit, oxidative stress also plays a pivotal role in the cognitive impairment of AD.…”
Section: Characterization Of Compoundmentioning
confidence: 99%
“…Several in vivo experiments indicated that BuChE is able to compensate for the lack of AChE, enabling continued regulation of cholinergic neurotransmission 19,20 . It has also been shown that cholinesterases display several non-classical properties associated with Ab and neurofibrillary tangles, and are therefore important for AD pathogenesis [21][22][23][24][25] . Recent studies have shown that BuChE exerts an influence on the modulation of motor control, awareness, cognition and behavior by regulation of ACh levels in the central nervous system (CNS) 26 .…”
Section: Introductionmentioning
confidence: 99%